Community Legal Awareness and Customary Sanction to Prevent Littering: How Penglipuran Village in Bali Makes Efforts?” - Ida Bagus Sudarma Putra (Faculty of law Udayana University, 2022)
Penglipuran is a customary village in Bali that traditionally imposes a customary sanction for villagers who litter waste in the territory of the village in the form of holding a prayascita ceremony. This article aims to analyze the existence of prayascita customary sanctions in Penglipuran Village, the efforts to overcome littering in the village territory, and the implications of such sanctions on the legal awareness of the community. This paper combines a religious based-research in social-humanities and empirical juridical research that analyzes data and legal sources in descriptive, qualitative, and systematic methods. This research revealed that prayascita customary sanction is imposed on anyone who is decided guilty for littering in a village meeting, entails that he/she has to hold a prayascita ceremony that takes place in the village’s catus pata (crossroad). The efforts of Penglipuran Village to tackle littering problems are overseeing and maintaining the sanctity, sustainability, cleanliness, and orderliness of the area of ??the village. The programs and facilities that are implemented to control littering practice in this article can be divided into preventive and repressive measures. In terms of legal awareness, the village community has generally obeyed the customary rules. It is proven by the absence of people who have been imposed prayascita customary sanctions. It may be assessed that village members have a high community legal awareness to sort waste and put it in the rubbish bin. Therefore, the sanction to hold a prayascita ceremony has never happened until now. This indicates that a clean living culture has been well internalized by the community.